New Medical Strategies for Midgut Carcinoids - Nilsson, Ola; Arvidsson, Yvonne; Johanson, Viktor; Forssell-Aronsson, Eva; Ahlman, Hakan (Anti-Cancer Agents in Medicinal Chemistry, 2010)
Patients with well-differentiated neuroendocrine tumours of the gastrointestinal tract often present with metastases and hormonal symptoms. These patients can be palliated by interventional tumour reduction and medical treatment with somatostatin analogues; no effective chemotherapy is available. Radionuclide therapy via somatostatin receptors is one new therapeutic alternative. The recognition that neuroendocrine tumours express specific receptors for growth factors and chemokines, which are of importance for tumour growth, vascularization, and spread, may open the way for new therapeutic approaches. The signalling pathways in carcinoid tumours are incompletely explored. This review summarizes potential new treatment strategies from clinical and experimental studies, e.g. inhibition of angiogenesis, targeting of growth factors or their receptors by tyrosine kinase inhibitors, interference with specific cellular pathways (mTOR, PI3K, RAS/RAF, Notch), and also inhibition of the proteasome and histone deacetylation. Combining targeted therapy with chemotherapy, or using drugs to sensitize for radionuclide therapy, may enhance the treatment outcome.
Keywords: growth factor receptor